2003
DOI: 10.1071/ar02174
|View full text |Cite
|
Sign up to set email alerts
|

Seed size and adventitious (nodal) roots as factors influencing the tolerance of wheat to waterlogging

Abstract: Abstract. In a glasshouse study, two experiments were conducted to understand how inherent variability, such as the seed size or mass, and formation of adventitious nodal roots might influence the tolerance of various wheat and triticale cultivars at different growth stages to waterlogging. Waterlogging at germination resulted in 11% seedling mortality, but the waterlogged seedlings had a 19% increase in shoot mass per plant, with no difference in root mass compared with non-waterlogged seedlings. Waterlogging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The result of our experiment support the aforesaid findings. Carbohydrate remaining after submergence will presumably be especially important in recovery growth after submergence (Singh and Singh, 2001;Ram et al, 2002;Das et al,2005).…”
Section: Total Sugar Content Of Leavesmentioning
confidence: 99%
“…The result of our experiment support the aforesaid findings. Carbohydrate remaining after submergence will presumably be especially important in recovery growth after submergence (Singh and Singh, 2001;Ram et al, 2002;Das et al,2005).…”
Section: Total Sugar Content Of Leavesmentioning
confidence: 99%
“…Evidence on the duration of this "head start" advantage is not consistent, possibly because seldom has this been tested in stressful or competitive environments, and results from greenhouse and Weld studies diVer depending on the environment, timing of emergence, and nutrient availability (Stanton 1984;Yanful and Maun 1996;Sousa et al 2003). Many studies have focused on agronomic or weedy species grown in fertile soils and have found that large seeds result in greater grain yield (Martincic et al 1997;Stougaard and Xue 2004), changed protein composition (Triboi et al 2003), better early performance (Kristensen 2003), higher rates of germination (Martincic et al 1997), and greater adventitious root growth under water-logged conditions (Singh and Singh 2003).…”
Section: Introductionmentioning
confidence: 96%
“…Seed mass effects could appear in the field, however, and the results of this greenhouse experiment may not be applicable to field conditions. Seed mass is related to germination success, seedling growth, and/or survival in several plant species (e.g., Howe and Richter 1982;Stanton 1984;Kromer and Gross 1987;Armstrong and Westoby 1993;Pimienta-Barrios et al 2002;Carter et al 2003;Debain et al 2003;Singh and Singh 2003;Petit et al 2009), although positive carryover effects sometimes decrease with age (Lo´pez et al 2003). Crist and Friese (1993) found that small seeds suffered more from decomposition and pathogens than did large seeds, across species; Moles et al (2003) and Campbell and Rochefort (2003) also observed increased sensitivity of buried small seeds compared to large seeds across species, but Pringle et al (2007) found the reverse.…”
Section: Effect Of Mixed Pollen Load On the Two Cactus Speciesmentioning
confidence: 91%